Cultural universality and specificity of teacher-student relationship: a qualitative study in Belgian, Chinese, and Italian primary school teachers - Xu, Canmei; Huizinga, Mariëtte; De Luca, Giuseppe; Pollé, Sophie; Liang, Ruwen; Sankalaite, Simona; Roorda, Debora L.; Baeyens, Dieter (Frontiers in Psychology, 2023)
This qualitative study investigated the teacher-student relationship (TSR) among 60 primary school teachers in Belgium, China, and Italy (i.e., countries with varying positions on the collectivistic-individualistic continuum of culture).Through semi-structured interviews and metatheme analysis, the study examined the similarities and differences in TSR across these countries, revealing a nuanced and diverse picture in various cultural contexts. The findings align with Pianta's model ( 2001) by including dimensions of closeness, conflict, and dependency, while also extending the model to identify additional dimensions such as authority, balance, distance, fairness, increasing student motivation, patience, and strictness. Regarding cultural perspective, teachers from these three countries exhibited similar conceptualizations of closeness, conflict, fairness, increasing student motivation, patience, and strictness, whereas the conceptualization of dependency, authority, balance, and distance may be influenced by (collectivistic versus individualistic) culture. Moreover, the manifestations of TSR varied across countries, highlighting the influence of cultural factors such as cultural norms, collectivistic versus individualistic values, and the perceived legitimacy of teacher authority. These findings shed light on the complexities of TSR across countries and emphasize the significance of culturally sensitive approaches in fostering positive TSR in education.